Labour and migration in rural Vietnam - Gaia Narciso (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper provides an overview of the characteristics of migrant households and analyses the effects of migration in Vietnam, on the basis of the Vietnam Access to Resources Household Survey conducted in 2012 and 2014. The data reveal significant movements of household members, both intra- and inter-province. Differences are uncovered between migrant and non-migrant households: migrant households are wealthier than non-migrant households, as measured by food expenditure. The analysis shows that remittances and migration act as a shock-coping mechanism, especially in the presence of natural shocks. Remittance recipient households seem to react better to natural shocks, as the remittance flows counterbalance the need for borrowing.
Keywords: J61; O1; 330; migration; remittances; Vietnam